2D europium coordination polymer as a regenerable fluorescence probe for efficiently detecting fipronil - Yang, Shuai-Liang; Lu, Jiu-Nan; Zhang, Sai-Jun; Zhang, Chen-Xi; Wang, Qing-Lun (Analyst (London), 2018)
Recently, considerable attention has been paid to European eggs that were found to contain the poisonous insecticide fipronil. Excessive consumption of fipronil can harm the human body, in particular, the liver, thyroid, nervous system and kidneys. As a consequence, there is an urgent need to develop a method to detect fipronil. In this work, a lanthanide coordination polymer [Eu(SIP)(H 2 O) 4 ] n ( 1 ) (NaH 2 SIP = 5-sulfoisophthalic acid monosodium salt) was synthesized and characterized by single-crystal X-ray crystallography, elemental analysis, infrared spectrum and powder X-ray diffractions. The X-ray studies show that 1 is a two-dimensional layered structure, which is constructed of fused {[Eu(H 2 O) 4 ] 3 (SIP) 3 } pseudo-hexagonal grids. The luminescence properties of 1 exhibit effective recognition for fipronil in methanol solution. Furthermore, a wide linear range (10 −6 -10 −4 M), a low detection limit of 0.8 μM, high selectivity and excellent recyclability, reveal that 1 can potentially act as a luminescence-based sensor for quantitative and highly sensitive detection of fipronil. To the best of our knowledge, it is the first time that a metal-organic coordination polymer, as a fluorescent-based probe, has been used for the detection of fipronil. Moreover, fluorescent-based test papers of 1 have also been prepared, which can be regarded as a simple and practical method for detecting fipronil. A metal organic coordination polymer based fluorescent probe was used to detect fipronil for the first time. Luminescence intensities of 1 continuously reduced with increasing concentrations of fipronil, and still showed high fluorescence intensity after four cycles.